2(3p+3)-2=4-2p

Simple and best practice solution for 2(3p+3)-2=4-2p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3p+3)-2=4-2p equation:


Simplifying
2(3p + 3) + -2 = 4 + -2p

Reorder the terms:
2(3 + 3p) + -2 = 4 + -2p
(3 * 2 + 3p * 2) + -2 = 4 + -2p
(6 + 6p) + -2 = 4 + -2p

Reorder the terms:
6 + -2 + 6p = 4 + -2p

Combine like terms: 6 + -2 = 4
4 + 6p = 4 + -2p

Add '-4' to each side of the equation.
4 + -4 + 6p = 4 + -4 + -2p

Combine like terms: 4 + -4 = 0
0 + 6p = 4 + -4 + -2p
6p = 4 + -4 + -2p

Combine like terms: 4 + -4 = 0
6p = 0 + -2p
6p = -2p

Solving
6p = -2p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '2p' to each side of the equation.
6p + 2p = -2p + 2p

Combine like terms: 6p + 2p = 8p
8p = -2p + 2p

Combine like terms: -2p + 2p = 0
8p = 0

Divide each side by '8'.
p = 0

Simplifying
p = 0

See similar equations:

| 30-7x=-12x | | 7(9-x)=91 | | 4(-7m+1)=4 | | 2y+y=10x-1 | | 4(-7x+9)=8 | | 7(-9-3x)=-294 | | 4(-4+7a)=96 | | 5(-2+4a)=190 | | V-3-2=-10 | | 101-(7x+12)=7(x+2)+x | | 15x+x=4x+3 | | -(1+7x)=3x-21 | | C/4+1/1=x-4/6 | | 7(4-6w)=-224 | | 4(10-4k)=-72 | | 2(6t+6)=-24 | | 7(1b+3)=105 | | 6(1-2n)=-126 | | 116+x+121=180 | | 3x+11+3x=3 | | 2r-3(r-7)=15 | | 3(-1b+1)=24 | | 2(2+7k)=60 | | 3(6-k)=-3 | | 16+x+121=180 | | 4x+7y=72 | | 16+x+12=180 | | 6(3+2h)=3(3h-2) | | 4x^2-19x+30=4x+2 | | 6(-7+7a)=-420 | | 6(3a+6)=-126 | | 3(8+2d)=84 |

Equations solver categories